2015
DOI: 10.1002/ps.4152
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and translocation of imidacloprid, clothianidin and flupyradifurone in seed‐treated soybeans

Abstract: This study enhances our understanding of the uptake and distribution of insecticides used as seed treatments in soybean. The uptake and translocation of these insecticides differed in response to soil moisture stress. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
4
32
0
1
Order By: Relevance
“…For oilseed rape seeds treated with clothianidin, plant bioavailability was 6% of clothianidin present in soil residues . These findings are consistent with similar resorption studies of imidacloprid in crop plants (Stamm et al 2016;Sur and Stork 2003), thus confirming that the bulk of systemic insecticides in coated seeds remains in the soil of the field. These findings raise serious questions about the poor efficiency of the system and the inevitable environmental contamination they produce Goulson 2013;Sánchez-Bayo 2017).…”
Section: Plants and Apicultural Producesupporting
confidence: 88%
See 1 more Smart Citation
“…For oilseed rape seeds treated with clothianidin, plant bioavailability was 6% of clothianidin present in soil residues . These findings are consistent with similar resorption studies of imidacloprid in crop plants (Stamm et al 2016;Sur and Stork 2003), thus confirming that the bulk of systemic insecticides in coated seeds remains in the soil of the field. These findings raise serious questions about the poor efficiency of the system and the inevitable environmental contamination they produce Goulson 2013;Sánchez-Bayo 2017).…”
Section: Plants and Apicultural Producesupporting
confidence: 88%
“…Stamm et al (2016) studied the uptake and translocation of imidacloprid, clothianidin, and flupyradifurone in seed-treated soybeans. They found that the novel flupyradifurone is absorbed at a higher rate during the early growth stage of the plant compared to clothianidin and imidacloprid.…”
Section: Plants and Apicultural Producementioning
confidence: 99%
“…Aside from the control by direct contact with the whitefly nymphs, systemic insecticides such as neonicotinoids (e.g., imidacloprid, acetamiprid, and thiamethoxam, commonly used for the control of hemipteran pests in Brazil) present high levels of vascular translocation inside the soybean plant (Stamm et al, 2016), being ingested by the whitefly nymph through its feeding and thus increasing the possibilities of control. Although more efficient when the insecticide is applied as seed treatment (Magalhaes et al, 2009), this effect may also be achieved via foliar application as long as the middle and lower thirds of the soybean plants are reached by the spraying, as the translocation of systemic insecticides occurs primarily from older to younger leaves (Bennett, 1957;Buchholz & Nauen, 2002).…”
Section: Implications On Sampling and Control Methods Of Bemisia Tabacimentioning
confidence: 99%
“…Sequential sprays are particularly important for the performance of pyrethroid insecticides, which rely basically on fast knockdown effect (Salgado, 2013); neonicotinoids, on the other hand, provide longer residual effect allied to robust plant sistemicity (Stamm et al, 2016), which may be linked to a higher control efficiency of nymphs, as observed in some of the treatments (e.g., acetamiprid in treatment T1). Whitefly nymphs infesting soybean are concentrated in the middle and lower thirds of the plants (Czepack et al, 2018), in the abaxial side of the leaflets and in the middle and bottom areas of its surface (Pozebon et al, 2019), due to the female's habit of feeding and ovipositing in the upper and younger leaves of the soybean plants; therefore, B. tabaci adults are more exposed to direct contact with the insecticide spray, while the control of the sheltered nymphs relies more heavily on the efficacy of the insecticide translocation inside the plant.…”
Section: Combined Analysismentioning
confidence: 99%